DEVELOPMENT OF ONLINE - BASED BEGINNER JOURNALISM LEARNING MODULES - Roni, Rahimin; Ali, Muhammad; Indriyani, Indriyani (Indonesian Journal of Educational Development (IJED), 2024)
The aim of developing an online-based journalism training module is to determine the effectiveness of using the module to improve online news writing skills. The research uses the Dick and Carey model. The target of the research was a small group of 7 journalists, and a large group of 15 journalists. Test targets for novice journalists on the Tribunjambi.com portal. The results of the small group test stated that it was good 50. Very good 48 and quite good 7. It was concluded that the module helped journalists write online news. In the large group test, the most statements were very good, there were 195. 26 statements were good and 4 statements were quite good. There are visible differences in the results of the small and large group choices. The results of small group tests are often selected as good statements. The results of the large group test after the revision of the module stated that many people chose very good. This means that the results of this trial after the module was revised were at a very good level, because 87 percent of the training participants chose statements in the very good category.